CSIG-13. CLINICAL IMPACT OF CDKN2A/B DELETIONS IN IDH-MUTANT ASTROCYTOMAS. (14th November 2022) - Yuile, Alexander; Satgunaseelan, Laveniya; Alexander, Kimberley L; Thavaneswaran, Subotheni; Krasovitsky, Michael; Buckland, Michael; Lee, Maggie; Wei, Grace; Kastelan, Marina; Wong, Mark; Wilson, Isabella; Bayly, Angela; et al.
Abstract: BACKGROUND: IDH-mutant astrocytomas with CDKN2A/B homozygous deletions (HD) are now categorized as grade 4 astrocytomas. It is unclear how these HD astrocytomas should be treated. We aimed to compare 3-year outcomes for HD versus heterozygous deleted (HeD) IDH-mutant astrocytomas, describe the prognostic impact of deletions relative to histologic grade and describe differences in outcomes based on treatment regimen. METHODS: Molecular and clinical data concerning IDH-mutant glioma patients +/- CDKN2A/B deletions were retrieved across four neuro-oncology centers and two tumor banks from 01/2016-07/2021. RESULTS: 48 patients with HD or HeD were identified. Median follow-up time was 4.0 years, median age 33 (range 20-74) years. Sixteen astrocytomas were histologic grade 4, remainder were grade 2 (n= 9) and grade 3 (n= 23). HD were detected in 16 patients. Survival data were unavailable in n= 1 HD and n= 2 HeD patients. 3-year OS for CDKN2A/B HD and HeD groups were 47% versus 67% (log-rank p= 0.004). For grades 2, 3 and 4, 3-year OS for HD were 100% (n= 1), 57% (n= 7) and 29% (n= 7) respectively, 3-year OS for HeD were 100% (n= 7), 56% (n= 16) and 57% (n= 7) respectively. In HD patients, six were treated with concurrent temozolomide-radiotherapy (3-year OS 50%) and five with radiotherapy and sequential temozolomide only (3-year OS 80%, log-rank p= 0.38). Treatment data were unavailable in two patients and three were treated with "other" regimens. Sequential regimens were preferentially used in histologic grade 2 and 3 cases. CONCLUSION: Preliminary data are in keeping with current literature and are one of the first to describe outcomes based on clinical regimen. There was insufficient evidence of OS differences between concurrent and sequential therapy, though conclusions are limited by sample size and data maturity. Additional follow-up data are required to further define optimal treatment for these patients.